Theory of thermal shock based on the generalized dynamic thermoelasticity model - E. M. Kartashov (Тонкие химические технологии)
The dynamic thermoelastic response of an area within a limited variety of geometric surfaces (planar, spherical, and cylindrical) was explored. A generalized dynamic model of thermoelasticity was formulated for these cases.